Dynamická in vivo 31P MR spektroskopie člověka - Hájek, Milan; Šedivý, Petr; Kovář, Jan; Dezortová, Monika (Chemické listy, 2017)
The constructions of super high (3T) and ultra high field (7T) magnetic resonance (MR) imagers in the past decade have enabled many MR imaging and spectroscopy experiments with other nuclei than protons. The paper summarizes the basis of in vivo dynamic 31P MR spectroscopy for biomedical and clinical applications. The calculations of quantitative parameters of muscular metabolism, such as pH, mitochondrial capacity, ADP concentration, time constant of phosphocreatine recovery and others, are shown. The construction of ergometers for the whole body magnetic resonance systems is described. Examples of typical data processing and evaluation are demonstrated.
Keywords: energetický metabolismus; Creatine Kinase, Mitochondrial Form; kreatinkinasa, mitochondriální forma; Ergometry; ergometrie; Muscle, Skeletal; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Hydrogen-Ion Concentration; svalová síla; mitochondriální kapacita; izotopy fosforu; koncentrace vodíkových iontů; kosterní svaly; Muscle Strength; kinetika; lidé; Energy Metabolism; Humans; tělesná námaha; Phosphorus Isotopes; Glycolysis; glykolýza; Kinetics; Physical Exertion; dynamická in vivo ³¹P MR spektroskopie